Mental and social health during and after acute emergencies: emerging consensus? - Mark van Ommeren; Shekhar Saxena; Benedetto Saraceno
Mental health care programmes during and after acute emergencies in resource-poor countries have been considered controversial. There is no agreement on the public health value of the post-traumatic stress disorder concept and no agreement on the appropriateness of vertical (separate) trauma-focused services. A range of social and mental health intervention strategies and principles seem, however, to have the broad support of expert opinion. Despite continuing debate, there is emerging agreement on what entails good public health practice in respect of mental health. In terms of early interventions, this agreement is exemplified by the recent inclusion of a "mental and social aspects of health" standard in the Sphere handbook's revision on minimal standards in disaster response. This affirmation of emerging agreement is important and should give clear messages to health planners.